A multi-staining chip using hydrophobic valves for exfoliative cytology in cancer. (13th June 2017) - Lee, Tae Hee; Bu, Jiyoon; Moon, Jung Eun; Kim, Young Jun; Kang, Yoon-Tae; Cho, Young-Ho; Kim, In Sik
Abstract: Exfoliative cytology is a highly established technique for the diagnosis of tumors. Various microfluidic devices have been developed to minimize the sample numbers by conjugating multiple antibodies in a single sample. However, the previous multi-staining devices require complex control lines and valves operated by external power sources, to deliver multiple antibodies separately for a single sample. In addition, most of these devices are composed of hydrophobic materials, causing unreliable results due to the non-specific binding of antibodies. Here, we present a multi-staining chip using hydrophobic valves, which is formed by the partial treatment of 2-hydroxyethyl methacrylate (HEMA). Our chip consists of a circular chamber, divided into six equal fan-shaped regions. Switchable injection ports are located at the center of the chamber and at the middle of the arc of each fan-shaped zone. Thus, our device is beneficial for minimizing the control lines, since pre-treatment solutions flow from the center to outer ports, while six different antibodies are introduced oppositely from the outer ports. Furthermore, hydrophobic narrow channels, connecting the central region and each of the six fan-shaped zones, are closed by capillary effect, thus preventing the fluidic mixing without external power sources. Meanwhile, HEMA treatment on the exterior region results in hydrophobic-to-hydrophilic transition and prevents the non-specific binding of antibodies. For the application, we measured the expression of six different antibodies in a single sample using our device. The expression levels of each antibody highly matched the conventional immunocytochemistry results. Our device enables cancer screening with a small number of antibodies for a single sample.